Dynamic seabed-anchor capacity enhancements for taut-moored floating offshore wind - Kwa, Katherine; White, David; Festa, Oscar; Gourvenec, Susan (Symposium on Energy Geotechnics 2023, 2023)
Decarbonisation of global energy supply to meet Net Zero targets by 2050 requires rapid expansion of offshore wind [4]. Much of this growth will come from floating offshore wind (FOW) technology where seabeds are less congested, high energy wind resources are located and conventional fixed offshore wind is not practical [1]. The required scale of FOW requires a step change in mooring and anchoring technology compared to existing hydrocarbon solutions. New, efficient and reliable mooring and anchoring systems are essential to economically deliver the necessary FOW [1]. Taut mooring arrangements can be attractive for FOW turbines as they require less length and lighter synthetic mooring line than traditional chain catenary mooring arrangements. However, taut moorings transmit significantly higher mean and peak tensions to the anchor compared to catenary moorings. It is therefore important to fully quantify the capacity available from anchors during typical FOW load conditions, including dynamic effects. This study focuses on how a numerical anchor macro model, Ancmac [6], can be used to capture and quantify dynamic anchor-seabed capacity benefits such as from seabed added mass, [5] and viscous soil strength effects. These effects can enhance the dynamic anchor capacity and are not typically considered in anchor design. Typical mooring-floater fluid-structure interaction analyses also model the connection of the mooring lines to the seabed as a fixed pin connection and so seabed-anchor-mooring interactions are not typically considered. Ancmac can replace this fixed pin connection node at the seabed as it uses mechanical analogue components (e.g. spring-viscous-slider and mass) to simply and practically link forces on the anchor with anchor and chain movements in the time domain to determine the seabed response and the current available anchor capacity. This study presents an example case where Ancmac is used to model the response of an embedded plate anchor that is subjected to a high amplitude, short period (= 6 and 10 s) high mean load event (Figure 1a). The anchor loads , , are derived from applying a 1-50 year storm design loading event on a 15MW FOW turbine [3] with a taut mooring line configuration composed of high modulus synthetic polyester rope [8]. Results show that if dynamic seabed benefits are not considered (purple line in Figure 1a), then a static anchor capacity of = 4.15 MN and corresponding anchor size of = 11.13 m2 is required (for an anchor buried in slightly overconsolidated soft clay =30 kPa and bearing capacity factor =12.42). If beneficial dynamic seabed enhancements are considered (shown by red lines ), then a lower initial static anchor capacity can be adopted =3.13 MN, which corresponds to a 25% decrease in the required anchor size (=8.41 m2). During the design loading event, as the applied anchor load, increases above the available static capacity, towards the maximum applied value, the anchor begins to move (Figure 1b) generating dynamic resistance from mobilising the non-linear viscous slider and added mass resistance components. The resistance in the viscous slider component is based on a model for the change in undrained strength with increasing equivalent strain rate (=, where is anchor diameter), as shown in Figure 1c. The resistance from the viscous slider component reaches a maximum at the time marked slightly after the peak of the applied mooring line loads, at time , as shown in Figure 1a-c. Reducing the period of the applied load (=10 s to 6 s) increased the added mass resistance as the anchor is subjected to higher accelerations. As a result, the anchor experienced significantly smaller (50% less) maximum displacement and reduced velocities. This comparison is also evident in Figure 1d, which compares the contributions of resistance forces from the spring-viscous-slider and added mass components. Ancmac can also capture the long-term enhancements in seabed strength and anchor capacity as a time-varying function of the life-cycle of seasonally varying, operational applied loads. This could, for example, further reduce the required anchor sizes, as can increase from beneficial long-term seabed consolidation effects [7]-[10]. These short and long-term seabed benefits that occur over the range of different loading timescales, and result in enhanced anchor capacities for loads that are relevant to FOW taut mooring configurations, will be further discussed during the presentation.